Pengembangan Modul Pembelajaran Fisika Berbasis Kearifan Lokal Pada Materi Suhu dan Kalor - Azizah Nur Safitri; Sarwanto Sarwanto; Dewanto Harjunowibowo (Jurnal Materi dan Pembelajaran Fisika, 2023)
The purpose of this research is to find out the characteristics of local wisdom-based physics learning modules on Temperature and Heat material, and to find out the feasibility of local wisdom-based physics learning modules on Temperature and Heat material so that it can be continued at the next test stage. The research method, namely Research & Development (R&D), uses the ADDIE instructional development model. In carrying out its development, the researcher carried out the first to third stages of the five development stages including the stages of analysis, design and development. The data sources included 2 experts, 2 reviewers, 10 students and 128 students who assessed the module from the material, media and language aspects. Referring to the results of the research and development of the module, the following conclusions are obtained: (1) the characteristics of the module being developed, printed modules that raise the phenomenon of local wisdom in the environment around students, are equipped with identification of initial abilities, descriptions of material, assignments, sample questions, and evaluations are then developed according to the nature of the module, namely self-instruction, self-contained, stand-alone, adaptive and user friendly; The physics module based on local wisdom on temperature and heat material is expected to make it easier for students to study physics material. This local wisdom-based physics learning module presents a description of the material as well as student activity sheets which are expected to make it easier for students both individually and in groups when formulating the concept of Temperature and Heat. (2) the feasibility value of the module has a very good category referring to expert validation with an average value of 93.2; reviewer validation gets an average value of 97.8; student validation obtained an average value of 97.8; the one-to-one trial obtained an average score of 93.8; small-scale trials 90.5; and field trials get an average value of 86.8.